Mini-Review: Syngas Production Via Partial Oxidation of Methane Reaction and Its Potential Catalyst - Silvana Dwi Nurherdiana; Reva Edra Nugraha; Rachmad Ramadhan Yogaswara; Hamzah Fansuri (LPPM, Institut Teknologi Sepuluh Nopember, 2021)
Methane as a light gas was generally found in natural gas which was burned freely to gain a high quality of petroleum. This action truly impacted a worst condition in nature, namely greenhouse effect. This brief review described fundamental theory of the important process in methane conversion from natural gas into value-added chemical such as syngas (CO+H2). The methane conversion reaction was commonly divided into direct and indirect reaction. The indirect reaction such as partial oxidation of methane was mostly chosen due to the intermediate product (syngas) can easily generate many raw materials of petrochemicals. This paper also described a potential catalyst to be applied which in heterogeneous type such as perovskite oxide, metal oxide and zeolite.